Development and application of molecular markers in fisheries, aquaculture, and industry of representative temperate and tropical sea cucumbers: a review - Liu, Xinghai; Tang, Xinyue; Chen, Muyan; Ni, Gang; Yang, Yujia (Frontiers in Marine Science, 2024)
Sea cucumber has emerged as a crucial economic species in aquaculture in China because of its remarkable nutritional and medicinal value. However, wild sea cucumber populations have experienced a decline due to overfishing and environmental factors, underscoring the urgent need for genetic resource conservation and biotechnology innovation within the sea cucumber aquaculture and breeding industry. The development of the sea cucumber industry is still impeded by challenges and difficulties. Nevertheless, significant progress has been made through the utilization of molecular markers, which have effectively addressed a number of fisheries and aquaculture issues. In recent years, diverse types of molecular markers including mitochondrial DNA, microsatellites, and SNP markers have been developed and extensively applied in various aspects of sea cucumber research. These markers play vital roles in genetic sex identification, germplasm resource evaluation, population structure assessment, as well as marker-assisted breeding in marine ranching and sea cucumber aquaculture and breeding industry. This review provides an overview of the fundamental principles, functions, and characteristics associated with various markers employed across various sea cucumber species while also discussing their applications within different aspects of the sea cucumber fisheries, aquaculture, and breeding industry.